The headman was a women the gender egalitarian Batek of Malaysia - Endicott, Kirk Michael; Endicott, Karen Lampell (Centre for Orang Asli Concerns, 2012)
A comprehensive ethnography of one of the few remaining hunting and gathering peoples of Southeast Asia, The Headman Was A Women presents the gender concepts, roles and relations of the highly egalitarian Batek of Peninsular Malaysia. Based on longtime fieldwork, the book describes the lives of Batek men and women in the tropical rainforest, and includes discussions of fieldwork, hunting and gathering, social organization, religion, gender, nonviolence, and cultural persistence in the face of a changing landscape. Rich in detail yet clearly written, The Headman Was a Woman introduces readers to an egalitarian people whose way of life is both thought-provoking and rare. The ethnography is accompanied by a 37-minute DVD, The Batek: Rainforest Foragers of Kelantan, Malaysia. Footage shows vivid highlights of camp life and social activities as well as all of the important economic processes described in the book.